Analisis Pengembangan Koleksi Perpustakaan Institut Teknologi Indonesia - Jaka Martian Rusmin (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The present study aims to investigate the process of collection development in the library of Institut Teknologi Indonesia. The researcher applies the six stages of collection development from Evans (2005) as the theoretical framework. The research method used in the study includes descritive analysis using the data, from interviews from its librarians, questionnaire and the additional observation to make the data more accurate. The result reveals that the library of Institut Teknologi Indonesia makes the most of community analysis, selection process, and the weeding process for the collection development activities. Yet, the library needs more efforts in making the policy and evaluation activity. Surprisingly, after comparing with other university libraries, it is found that those libraries do not have formal and systematic policies of collection development, and they also barely conduct the evaluation meetings after the collection development activity is completed. The contribution from the stakeholders and incumbents are needed to escalate the collection development in the library.